KONTRIBUSI PERUSAHAAN HTI PT. RIMBA PERANAPINDAH DALAM KONSERVASI GAJAH DI AREAL KONSESIPERUSAHAAN - Rinta Hermiza Ningsih; Defri Yoza; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Sumatran elephant conservation must be improved, so the research was conducted with the aim of knowing the contribution of the PT. Forest of Peranap Indah in Sumatran Elephant conservation in the concession area of PT. Beautiful Peranap Jungle. The method in this study is data processing using descriptive analysis using library research data collection techniques, field studies, namely spatial observation, Sumatran elephant roaming paths, habitat protection, Sumatran elephant conservation personnel, Sumatran elephant food costs for conservation management, interviews and questionnaires. The data analysis technique is the examination stage, the coding stage, the testing stage and the data describing stage. The results of observations made are PT. Forest of Peranap Indah Contributes to Elephant Conservation in the Company's concession area. The conclusion of this researcher is PT. Forest of Peranap Indah contributes to Sumatran Elephant conservation activities in its concession area. Contribution of PT. Jungle Peranap Indah in Sumatran Elephant Conservation in the area in the form of providing protected areas, having conservation officers, conducting patrols, planting additional feed for animals, namely bananas, sugar cane and bamboo, and having costs in conservation activities. Keywords: Sumatran elephants, contribution, PT. Rimba Peranap Indah